2013
DOI: 10.1051/0004-6361/201321416
|View full text |Cite
|
Sign up to set email alerts
|

SimultaneousXMM-Newtonand HST-COS observation of 1H0419-577

Abstract: In this paper we analyze the X-ray, UV, and optical data of the Seyfert 1.5 galaxy 1H0419-577 with the aim of detecting and studying an ionized-gas outflow. The source was observed simultaneously in the X-rays with XMM-Newton and in the UV with HST-COS. Optical data were also acquired with the XMM-Newton Optical Monitor. We detected a thin, lowly ionized warm absorber (log ξ ≈ 0.03, log N H ≈ 19.9 cm −2 ) in the X-ray spectrum, which is consistent to be produced by the same outflow already detected in the UV. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 61 publications
5
29
0
Order By: Relevance
“…We can conclude that no warm absorber or at least an even smaller column (N H ≈ 10 20 cm −2 ) is required for the MF state. The result matches the RGS spectral analysis of the MF observations (N H ≈ 10 19.9 cm −2 ) in Di Gesu et al (2013). The warm absorber in the HF state can account for the spectral difference between the MF and HF spectra at the 0.6-0.8 keV band, in addition to the continuum variability.…”
Section: Multi-epoch Spectral Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…We can conclude that no warm absorber or at least an even smaller column (N H ≈ 10 20 cm −2 ) is required for the MF state. The result matches the RGS spectral analysis of the MF observations (N H ≈ 10 19.9 cm −2 ) in Di Gesu et al (2013). The warm absorber in the HF state can account for the spectral difference between the MF and HF spectra at the 0.6-0.8 keV band, in addition to the continuum variability.…”
Section: Multi-epoch Spectral Analysissupporting
confidence: 85%
“…Also a variable power-law continuum emission in the high energy band was noticed in later XMM-Newton observations (Pounds et al 2004a,b;Pounds 2005). A long XMM-Newton observation in 2010 shows a thin, lowly ionized warm absorber in its high resolution grating spectrum (Di Gesu et al 2013). By fitting the XMM-Newton spectrum at an extreme low flux state with the relativistic reflection model, Fabian et al (2005) obtained a disc inner radius of r in < 2r g , indicating a black hole spin of a * > 0.95.…”
Section: Introductionmentioning
confidence: 99%
“…1). In the Reflection Grating Spectrometer (RGS) spectrum of this dataset (already presented in Di Gesu et al 2013, hereafter Paper I) we detected a lowly ionized absorbing gas (also observed in Suzaku, Winter et al 2012). We found that the X-ray and the UV absorbing gas (Edmonds et al 2011) are consistent to be one and the same.…”
Section: H 0419-577: a Variable Seyfert Galaxysupporting
confidence: 53%
“…Multi-waveband campaigns A&A 589, A76 (2016) provided the detailed broad-band spectrum and the timedependent behavior of X-ray outflows in a number of bright Seyfert-1 galaxies: NGC 7469 , NGC 5548 Kaastra et al 2004;Steenbrugge et al 2005), Mrk 509 Steenbrugge et al 2011;Kaastra et al 2011Kaastra et al , 2012Ebrero et al 2011;Arav et al 2012), IRAS 13449+2438 (Lee et al 2013;Di Gesu et al 2013, NGC 3783 (Kaspi et al 2002;Gabel et al 2003;Netzer et al 2003).…”
Section: Introductionmentioning
confidence: 99%